Self-Satisfaction Towards the Academic Specialization and its Relationship to the Level of Ambition Among Special Education Female Students at Al Asmariya University, Zliten, Libya (Journal of Humanitarian and Applied Sciences, 2023)
Abstract:Abstract The aim of the current study is to identify the level of self-satisfaction towards the academic specialization and its relationship to the level of ambition among special education female students in the Human Science College at Al Asmariya university. This study will found out the satisfaction scale differences about the academic specialization and the level of ambition among the subjects of the study which depends on the academic level of the students. The study included a random sample of about (63) female students. The participants of the study are selected from the first and the last semester during the academic year 2022-2023. A questionnaire is used for data collection. The findings of the study are analyzed in a descriptive way. The findings of the study revealed that there is a percentage of satisfaction among the participants of the study towards their academic specialization. The results also showed that there is a high level of satisfaction about the learning major and the ambition level of the students. Last but not least, the study found that there is a positive relationship between the level of ambition and the students satisfaction towards their specialization. Finally, the study pointed out that there is not any differences between the satisfaction towards the academic specialization and the level of ambition among the students of both semesters (the first and the last).
Keywords: self-satisfaction towards the academic specialization; special education female students; level of ambition.